'Differences between the earth and the sky': migrant parents' experiences of child health services for pre-school children in the UK. (17th August 2020) - Condon, Louise; McClean, Stuart; McRae, Luiza
Abstract: Aim: To explore parents' experiences of using child health services for their pre-school children post-migration. Background: Migrating between countries necessitates movement and adjustment between systems of healthcare. Children of migrants are known to have poorer health than local children on some measures and are less likely to access primary care. In the United Kingdom (UK), children are offered a preventive Healthy Child programme in addition to reactive services; this programme consists of health reviews and immunisations with some contacts delivered in the home by public health nurses. Methods: Five focus groups were held in a city in South West England. Participants were parents of pre-school children (n = 28) who had migrated to the UK from Romania, Poland, Pakistan or Somalia within the last 10 years. Groups selected included both 'new migrants' (from countries which acceded to the European Union in the 2000s) and those from communities long-established in the UK (Somali and Pakistani). One focus group consisted of parents of Roma ethnicity. Interpreters co-facilitated focus groups. Findings: Participants described profound differences between child health services in the UK and in their country of origin, with the extent of difference varying according to nationality and ethnic group. All appreciated services free at the point of delivery and an equitable service offered to all children. Primary care services such as treatment of minor illness and immunisation were familiar, but most parents expected doctors rather than nurses to deliver these. Proactive child health promotion was unfamiliar, and some perceived this service as intruding on parental autonomy. Migrants are not a homogenous group, but there are commonalities in migrant parents' experiences of UK child health services. When adjusting to a new healthcare system, migrants negotiate differences in service provision and also a changing relationship between family and state.